2012
DOI: 10.1002/hep.24804
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic hepatitis B among foreign-born persons living in the United States by country of origin

Abstract: Estimates of the prevalence of chronic hepatitis B (CHB) in the United States differ significantly, and the contribution of foreign-born (FB) persons has not been adequately described. The aim of this study was to estimate the number of FB persons in the United States living with CHB by their country of origin. We performed a systematic review for reports of HBsAg seroprevalence rates in 102 countries (covering PubMed from 1980 to July 2010). Data from 1,373 articles meeting inclusion criteria were extracted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
340
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(354 citation statements)
references
References 16 publications
12
340
1
1
Order By: Relevance
“…From the 1 Gastroenterology Section, and 2 Center for Health Equity Research and Promotion, Philadelphia VA Medical Center, Philadelphia, PA; 3 Division of Gastroenterology, Department of Medicine, Hospital of the University of Pennsylvania, Philadelphia, PA; 4 Center for Clinical Epidemiology and Biostatistics, Perelman School of Medicine at the University of Pennsylvania, Philadelphia, PA.…”
Section: Article Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 1 Gastroenterology Section, and 2 Center for Health Equity Research and Promotion, Philadelphia VA Medical Center, Philadelphia, PA; 3 Division of Gastroenterology, Department of Medicine, Hospital of the University of Pennsylvania, Philadelphia, PA; 4 Center for Clinical Epidemiology and Biostatistics, Perelman School of Medicine at the University of Pennsylvania, Philadelphia, PA.…”
Section: Article Informationmentioning
confidence: 99%
“…In the United States, the prevalence of chronic hepatitis B remains incompletely quantified, with estimates ranging from approximately 800,000 individuals to as high as 2.2 million when including foreign-born Americans. (1,2) Chronic HBV infection is a significant cause of morbidity and mortality, leading to liver failure, cirrhosis, and hepatocellular carcinoma (HCC) in 25%-40% of infected persons. (3) Specifically, in the United States, hepatitis B is the underlying cause of an estimated 1800-4000 deaths each year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported the prevalence of hepatitis infection among Cambodians. The reported prevalence varied largely among different geographical areas and different periods of survey; 7.7% to 11.8% for HBV and 2.3% to 14.7% for HCV (Thuring et al, 1993;Sarmati et al, 2003;Buchy et al, 2004;Caruana, 2005;Ha et al, 2009;Sann et al, 2009;Sa-Nguanmoo, 2010;Akkarathamrongsin et al, 2011;Kowdley et al, 2012). Among those with elevated serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) measured at Pasteur Institute Phnom Penh, 41% and 39% were found to be positive for HBV antigen and HCV antibody, respectively (Buchy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 High rates of chronic hepatitis B among the US foreign born reflect the large global burden of hepatitis B, 370 million persons around the world, and the migration to the US from countries where prevalence of hepatitis B virus (HBV) is highest. More than 60% of new immigrants to the US come from countries of increased hepatitis B endemicity (hepatitis B surface antigen [HBsAg] prevalence of 2%).…”
mentioning
confidence: 99%